ANALISIS FAKTOR-FAKTOR PENYEBAB MEROKOK PADA MAHASISWA FKIP UNTAN PONTIANAK TAHUN AJARAN 2019/2020 - Hadi Tomi; Yuline Yuline; Luhur Wicaksono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe and find out about the Characteristics, Factors that cause smoking, and any Impact that arises on FKIP UNTAN Pontianak students in the academic year 2019/2020. This research method is a descriptive method with a form of survey research. The population in this study is an active student of FKIP UNTAN Pontianak academic year 2019/2020 class 2017 which is a total of 69 male students. This study uses a quantitative approach with indirect communication data collection techniques, and the data collection tools used are questionnaires. Based on the results of this study shows that the factors that cause smoking in FKIP UNTAN Pontianak students in the academic year 2019/2020 are in the category "High enough". (1) Characteristics of student smokers with the highest percentage of clothing and mouth smelling of 83.47%, teeth and fingers yellowing 76.66%, loss of eye clarity 66.08%, appearance of wrinkles on the forehead, tip of the lips and under the eyes 65.7 %, obtained the overall result of 72.93% with the category "High enough". (2) Internal factors that cause smoking in students with the highest percentage of addiction and addiction 80.09%, reactions to emotional decline 74.46%, positive emotional reactions 73.14%, social reasons 62.99%, obtained overall results namely 73.27% with the category "Highly High". (3) External factors that cause smoking in students with the highest percentage of peer influence 71.81%, social environment 67.18%, parental influence 58.16%, obtained overall results of 66.56% with the category "High enough" , (4) The negative impact and danger of smoking felt by students with the highest percentage is the negative impact of smoking in terms of health 70.14%, the danger of smoking in the social, economic and environmental fields 69.44% obtained overall results of 69.79% with category Ckup Tinggi ”. Based on the above description, it can be generally known that the factors that cause smoking in FKIP UNTAN Pontianak students in the academic year 2019/2020, overall obtained 70.67% with the category "High enough". This shows that the factors that cause smoking in FKIP UNTAN Pontianak students are quite high.Keywords: Analysis, Causes of Smoking